TINDAK GEN KETAHANAN TERHADAP PENYAKIT KARAT (Pucinnia arachidis, Speg.) PADA KACANG TANAH - Juli Santoso (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2007)
The rust disease resistance of groundnut has inherited pattern 9 : 7, indicating that was controlled by double resessive genes. From this fact needs an explanation of gene action, so it can be used as information in the breeding system and selection. The purpose of this research is to know the gene action control, if resistant the rust disease in groundnut. The design used in this experiment was randomized block design with three replications. There were 29 genotypes as treatments (5 genotypes parents, 6 genotypes F1, 6 genotypes F2, 6 genotypes BC1.1 and 6 genotypes BC1.2). The result of the experiment showed that there was a gene non-allelic interaction, mean effect (m) and a dominant gene effect (h) in progeny of Muneng x ICGV 87358 (Six Parameters Mode). However, the gene non-ellelic interaction did not occur in other progenies. Meanwhile progenies of Gajah x ICGV 92088, Gajah x ICGV 87358, Gajah x ICGV 91227 had a mean effect (m) and a aditive gene effect (d), and Muneng x ICGV 92088, Muneng x ICGV 91227 had only a mean effect (m).